ChemInform Abstract: A Convenient Synthesis of Phosphonomethyl α, β‐Unsaturated γ‐Lactams. Issue 4 (January 2016) - Abdelli, Abderrahmen; Efrit, Mohamed Lotfi; Gaucher, Anne; M'rabet, Hedi; Prim, Damien
Abstract: An efficient method for the preparation of a novel family of functionalized phosphonomethyl α, β‐unsaturated γ‐lactams is established.